Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09